Direct democracy: What if there is a conflict between the will of the people and fundamental rights? A comparative analysis between Switzerland and California - Josi, Claudia (2015)
In many countries, citizens have the power to propose new laws oramendments to their constitutions by popular initiatives. Provided that they have a special legitimacy, they are often regulated by different procedures to the legislation enacted by the legislature and may be used by their proponents to avoid the restrictions that the “ordinary” legislation is subject to. Recently, this has led that several popular initiatives which have come into conflict with the rights of minorities, fundamental rights of other affected groups, and other constitutional guarantees have been submitted. From the perspective of a comparative analysis, this article explores whether the laws in Switzerland and California set the procedural and substantive restrictions to this mechanism of direct democracy and to what extent. In this context, the author questionswhether the scope and enjoyment of fundamental rights may be subject to popular initiatives. Finally, several recommendations are made to improve the legal limits of popular initiatives and their control mechanisms to ensure that the scope and enjoyment of fundamental rights are not subject to the contentof popular initiatives.